The Clinical Effectiveness of Cognitive Therapy for Depression in an Outpatient Clinic - Gibbons, Carly J. (2010)
BACKGROUND: Cognitive therapy (CT) has been shown to be efficacious in the treatment of depression in numerous randomized controlled trials (RCTs). However, little evidence is available that speaks to the effectiveness of this treatment under routine clinical conditions. METHOD: This paper examines outcomes of depressed individuals seeking cognitive therapy at an outpatient clinic (N = 217, Center for Cognitive Therapy; CCT). Outcomes were then compared to those of participants in a large NIMH-funded RCT of cognitive therapy and medications as treatments for depression. RESULTS: The CCT is shown to be a clinically representative setting, and 61% of participants experienced reliable change in symptoms over the course of treatment; of those, 45% (36% of the total sample) met criteria for recovery by the end of treatment. Participants at CCT had similar outcomes to participants treated in the RCT, but there was some evidence that those with more severe symptoms at intake demonstrated greater improvement in the RCT than their counterparts at CCT. LIMITATIONS: The CCT may not be representative of all outpatient settings, and the structure of treatment there was considerably different from that in the RCT. Treatment fidelity was not assessed at CCT. CONCLUSIONS: Depressed individuals treated with cognitive therapy in a routine clinical care setting showed a significant improvement in symptoms. When compared with outcomes evidenced in RCTs, there was little evidence of superior outcomes in either setting. However, for more severe participants, outcomes were found to be superior when treatment was delivered within an RCT than in an outpatient setting. Clinicians treating such patients in non-research settings may thus benefit from making modifications to treatment protocols to more closely resemble research settings.